Predictors of Staff Turnover and Turnover Intentions within Addiction Treatment Settings: Change over Time Matters. (January 2014) - Garner, Bryan R.; Hunter, Brooke D.
This study examined the extent to which changes over time in clinicians' responses to measures of work attitude (eg, job satisfaction) and psychological climate (eg, supervisor support) could predict actual turnover and turnover intentions above and beyond absolute levels of these respective measures. Longitudinal data for this study were collected from a sample of clinicians ( N = 96) being trained to implement an evidence-based treatment for adolescent substance use disorders. Supporting findings from a recent staff turnover study, we found job satisfaction change was able to predict actual turnover above and beyond average levels of job satisfaction. Representing new contributions to the staff turnover literature, we also found that change over time in several other key measures (eg, job satisfaction, role manageability, role clarity) explained a significant amount of variance in turnover intentions above and beyond the absolute level of each respective measure. A key implication of the current study is that organizations seeking to improve their ability to assess risk for staff turnover may want to consider assessing staff at multiple points in time in order to identify systematic changes in key employee attitudes like turnover intentions and job satisfaction.